Analysis of Curriculum Policy Development and Implementation of Independent Curriculum in Elementary Schools - Fitriyani Fitriyani; Ira Restu Kurnia; Siska Nur Fadillah; Anna Maria Oktaviani (Journal of Education and Teaching Learning, 2023)
This research is to find out and examine the "Analysis of the Implementation of the Independent Curriculum in SDIT Citra Insani Driving School, Cikarang. This research was conducted using a phenomenological approach. This type of research is qualitative research that looks and hears more closely and in detail an individual's explanation and understanding of his or her experiences. The phenomenological approach is based on the interest of researchers to study more deeply about the phenomena experienced by key informants. The research was conducted at SDIT Citra Insani, Cikarang. The informants in this study were teachers, principals, supervisors. Data collection is carried out by several techniques, namely; (a) observation; (b) interviews; and (c) documentation studies To ensure the validity of the data is carried out with several efforts as follows: (a) extending the data collection period, (b) making continuous and earnest observations, (c) triangulating, and (d) involving colleagues to discuss. From the results of the study in this study, it was found that there is an independent curriculum that is a reference in driving schools, which produces students who believe and are devoted to the One God and have noble morals, Global diversity, mutual assistance, independence, creativity, and critical reasoning. The driving principals encourage a wide variety of participatory, unique and innovative programs. Fostering cooperation with teachers who support their leaders in participating in realizing mobilizing schools.